Soil carbon and nitrogen mineralization caused by pig slurry application under different soil tillage systems - Balota,Elcio Liborio (2010)
The objective of this work was to evaluate the change in soil C and N mineralization due to successive pig slurry application under conventional tillage (CT) and no tillage (NT) systems. The experiment was carried out in a clayey Latossolo Vermelho eutrófico (Rhodic Eutrudox) in Palotina, PR, Brazil. Increasing doses of pig slurry (0, 30, 60 and 120 m³ ha-1 per year) were applied in both tillage systems, with three replicates. Half of the pig slurry was applied before summer soil preparation, and the other half before the winter crop season. The areas were cultivated with soybean (Glycine max L.) and maize (Zea mays L.) in the summers of 1998 and 1999, respectively, and with wheat (Triticum sativum Lam.) in the winters of both years. Soil samples were collected at 0-5, 5-10, and 10-20 cm depths. Under both CT and NT systems, pig slurry application increased C and N mineralization. However, increasing pig slurry additions decreased the C to N mineralization ratio. Under the NT system, C and N mineralization was greater than in CT system.